2020
DOI: 10.1101/2020.08.07.20166389
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The emergence of azithromycin-resistant Salmonella Typhi in Nepal

Abstract: Typhoid fever remains a significant cause of morbidity and mortality in Asia and Africa. The emergence of azithromycin resistance in South Asia is concerning, as azithromycin is one of the last effective oral drugs for treating typhoid. In mid-2019, three azithromycin-resistant (AzithR) S. Typhi isolates were isolated from typhoid fever patients attending Patan Hospital, Kathmandu, Nepal. These organisms were whole genome sequenced and compared with a global collection. We found that the three AzithR isolates … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…To gain further genomic and evolutionary insight into the AcrB-717 mutations of Salmonella Typhi, we contextualized 33 AcrB-R717Q/L and 47 AcrB-717WT isolates collected in the same study in a maximum-likelihood phylogenetic tree against 750 Salmonella Typhi genomes reported from Bangladesh in previous studies ( 14 , 18 , 21 , 22 ) (see Table S2 ). These previous studies included 12 genomes with AcrB-R717Q/L mutations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To gain further genomic and evolutionary insight into the AcrB-717 mutations of Salmonella Typhi, we contextualized 33 AcrB-R717Q/L and 47 AcrB-717WT isolates collected in the same study in a maximum-likelihood phylogenetic tree against 750 Salmonella Typhi genomes reported from Bangladesh in previous studies ( 14 , 18 , 21 , 22 ) (see Table S2 ). These previous studies included 12 genomes with AcrB-R717Q/L mutations.…”
Section: Resultsmentioning
confidence: 99%
“…These previous studies included 12 genomes with AcrB-R717Q/L mutations. In addition, the tree also included five AcrB-717 mutants previously identified in the United Kingdom, Nepal, and Pakistan ( 16 18 ). The final tree contained 50 Salmonella Typhi genomes with AcrB-R717Q/L.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, they found 13 out of 1,082 strains with azithromycin resistance levels between 32-64 μg/ml, of which 12 harbored the R717Q/L mutation in the AcrB multidrug efflux pump (19). Similarly, in a recent study, S. Typhi isolates from Nepal from 2019 harboring the R717L mutation were non-susceptible to azithromycin (15). Genomic analysis of 133 S. Typhi strains collected in India between 1993 and 2016 showed that the two azithromycin non-susceptible strains contained the R717Q mutation in AcrB (20).…”
Section: Introductionmentioning
confidence: 90%
“…These substitutions are present in the efflux pump's proximal binding pocket (11)(12)(13) at the Channel 2 entrance (12)(13)(14). This is a concerning development, as in many countries, azithromycin is the last available and effective oral drug to treat typhoid (15,16). In 2010, the first azithromycin-resistant S. Serovars Paratyphi A strains unresponsive to azithromycin treatment isolated from Pakistan were reported (17).…”
Section: Introductionmentioning
confidence: 99%